Assessing the Candida in Healthy Subjects and Subjects with Oral Submucous Fibrosis: A Comparative Clinical Study: Life Sciences-Microbiology - Deshkar, Smita; Gaigawale, Anushree S; Rangari, Priyadarshini; Raj, Anil; Aggarwal, Charul; Tyagi, Garima (International Journal of Life Science and Pharma Research, 2022)
One precancerous condition with a high potential to turn into malignancy and pose a high risk is OSMF (oral submucous fibrosis) which mainly affects the young subjects globally as well as in India. The etiology of OSMF is attributed to the gutkha chewing habit. Another predominant etiologic factor governing the etiopathogenesis of malignant and premalignant lesions is the Candida species. Our aim of the present clinical study was conducted to assess and compare the intensity and incidence of Candida species in healthy subjects and subjects with oral submucous fibrosis. This study included 24 healthy controls and 24 subjects with a confirmed diagnosis of OSMF. A detailed history was recorded and a clinical examination was done for all the study subjects. All the samples were obtained from the oral rinse and were cultured using Sabouraud’s agar medium followed by identification and counting of isolated yeast species on sugar assimilation test, chlamydospore formation, and germ tube test. In the OSMF group, Candida species were isolated from 41.66% (n=10) of subjects. However, in the control group, Candida species were isolated from 16.66% (n=4) of the collected samples. This identification difference showed that higher species were isolated from the OSMF group compared to the control group (p=0.07). In the OSMF group, CFU/ml had a range of 500-970 with mean CFU values of 721.27±143.88. In the control group, the CFU/ml range was 60-320, whereas, the mean CFU/ml value was 186.64±130.10. The mean value was higher in the OSMF group compared to the control group. This difference was statistically significant with a p-value of 0.005. The present study concludes that the intensity and incidence of C. Albicans, candida species was higher in subjects with OSMF compared to healthy controls, however, these species were in the normal range of 3% to 47%. Hence, Candida cannot be considered an etiologic factor for transforming OSMF into a malignant lesion. However, further evaluation is needed to evaluate if betel quid chewing in subjects with OSMF promotes or inhibits the invasion and adherence of Candida species.